Wolność w liberalizmie a prawda o wolności - Ślipko SJ, ks. Tadeusz (Annales. Etyka w Życiu Gospodarczym, 2008)
The freedom, in Latin libertas, is the object of philosophical reflection since Plato. Yet asthe determined philosophical direction it took the form of the „liberalism” on the turning point ofthe sixteenth and seventeenth century, represented by two philosophers: Thomas Hobbes (1588–1679)and Jean-Jacques Rousseau (1712–1778). Among contemporary scholars Isaiah Berlin is standing out.From his point of view the philosophical problem of the freedom should be examined in two aspects:the negative freedom i.e. the attribute of not hindered freedom in making choices and the positivefreedom as opportunity of being the master of one’s own fate. The author of the article, after criticaldemonstrating the conception of liberalism, sketches the theory of freedom from the position ofChristian ethics. As a starting point he takes the conception of man as a person whose rational activitiestake on the form of twofold freedom of choice. In the psychological aspect, this freedom assumesthe ambivalent form of doing good or evil, however in the moral aspect it turns out to be freedom put inorder by the hierarchy of objective moral values. In this meaning the freedom also organizes the wholefree man's activity and becomes creative strength of his moral personal perfection. It also definesthe crucial sense of Christian philosophical science of truth about freedom.